2020
DOI: 10.3390/cells9081827
|View full text |Cite
|
Sign up to set email alerts
|

Tat-Cannabinoid Receptor Interacting Protein Reduces Ischemia-Induced Neuronal Damage and Its Possible Relationship with 14-3-3η

Abstract: Cannabinoid receptor-interacting protein 1a (CRIP1a) binds to the C-terminal domain of cannabinoid 1 receptor (CB1R) and regulates CB1R activities. In this study, we made Tat-CRIP1a fusion proteins to enhance CRIP1a penetration into neurons and brain and to evaluate the function of CRIP1a in neuroprotection following oxidative stress in HT22 hippocampal cells and transient forebrain ischemia in gerbils. Purified exogenous Tat-CRIP1a was penetrated into HT22 cells in a time and concentration-dependent manner an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Tat ( trans -acting activator of transcription) was discovered in human immunodeficiency virus-1, and it is widely used to deliver proteins, DNA phages, and liposomes intracellularly [ 22 , 23 , 24 ]. In addition, Tat-cargo fusion proteins are successfully delivered into the hippocampus [ 25 ], and they show neuroprotective effects against ischemic damage [ 26 , 27 ]. Several studies have demonstrated that the Tat-p27 fusion protein is efficiently delivered to cardiomyocytes, and treatment with Tat-p27 protects cardiomyocytes from myocardial infarction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tat ( trans -acting activator of transcription) was discovered in human immunodeficiency virus-1, and it is widely used to deliver proteins, DNA phages, and liposomes intracellularly [ 22 , 23 , 24 ]. In addition, Tat-cargo fusion proteins are successfully delivered into the hippocampus [ 25 ], and they show neuroprotective effects against ischemic damage [ 26 , 27 ]. Several studies have demonstrated that the Tat-p27 fusion protein is efficiently delivered to cardiomyocytes, and treatment with Tat-p27 protects cardiomyocytes from myocardial infarction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transformed proteins were harvested after disruption with 5 mM imidazole, 0.5 M NaCl, and 20 mM Tris-HCl (pH 7.9) containing 6 M urea. Proteins were purified using Ni 2+ -nitrilotriacetic acid Sepharose affinity column (Qiagen, Valencia, CA, USA) and PD-10 column chromatography, and the purified protein was identified by western blotting for His-tag, as previously described 24,25 .…”
Section: Synthesis Of Tat-mdh1 and Its Control Proteinmentioning
confidence: 99%
“…Thereafter, the membranes were incubated with mouse anti-His-tag (1:1,000; Abcam, Cambridge, UK) and mouse anti-β-actin (1:5,000; Cell Signaling, Danvers, MA, USA). After washing the membranes, the protein bands were visualized using chemiluminescent reagents as previously described 25,26 .…”
Section: Confirmation Of Tat-mdh1 Delivery In Ht22 Cells and The Gerb...mentioning
confidence: 99%
See 2 more Smart Citations